Interactive Gamification Based Learning Videos to Improve Indonesian Language Learning Outcomes of Third Grade Students - Ni Komang Anik Warsani; Maria Goreti Rini Kristiantari; Chindytia (International Journal of Language and Literature, 2026)
This research is motivated by the low learning outcomes of third-grade elementary school students in Indonesian language subjects, especially active and passive sentences, which indicates that the learning process has not been able to optimally increase student engagement and motivation. This problem requires the development of learning media that are more interesting, interactive, and appropriate to the characteristics of elementary school students. This research aims to produce interactive video media based on gamification that is feasible and effective in improving student learning outcomes. This research is a development research that refers to the ADDIE model with research subjects including content experts, media experts, learning design experts, teachers, and third-grade elementary school students. Data collection was carried out through observation, interviews, questionnaires, and tests using instruments in the form of validation sheets, teacher and student response questionnaires, and learning outcome tests. Data analysis used descriptive quantitative techniques, descriptive qualitative, and inferential statistical tests. The results of the study showed that the developed media obtained very feasible qualifications based on expert, teacher, and student assessments, and was proven effective in improving student learning outcomes after the use of learning media. This study concluded that interactive video media based on gamification is able to create more active, interesting, and meaningful learning. The implication is that this media can be used as an alternative innovation in Indonesian language learning to increase motivation, participation, and learning outcomes of elementary school students.